Yinhua Gouteng decoction alleviates tic disorder symptoms by modulating neuro-inflammation in a rat model - Hu, Mingge; Yang, Yan; Wang, Shuxia; Huang, LiRong; Chen, Lifei; Zhang, Xinguang; Yao, Wenbo; Xue, Zheng (Frontiers in Immunology, 2026)
BackgroundTic disorders (TDs) are childhood-onset neurodevelopmental disorders characterized by complex neurochemical dysregulation, and inflammation plays a critical role in TD pathogenesis. Yinhua Gouteng Decoction (YHGTD), a traditional Chinese medicinal formula, has demonstrated clinical efficacy in TD management. However, the specific pharmacological mechanisms underlying its effects remain unclear. In this study, we investigated the neuroprotective and anti-inflammatory effects of YHGTD in a 3,3′-iminodipropionitrile (IDPN)-induced TD rat model.MethodsA rat model of IDPN-induced was established. Behavioral assessments, striatal histopathology, and quantification of striatal dopamine (DA) levels and dopamine receptor (DR) expression were measured to assess the effects of YHGTD on tic symptoms and dopaminergic function. Microglial activation was examined by immunofluorescence staining, while IL-1β, TNF-α, and IL-6 in serum, striatum, and colon were quantified using ELISA or qPCR. In addition, 16S rRNA sequencing was used to analyze alterations in the gut microbiota composition. Western blotting was performed to assess TLR4/MyD88/NF-κB pathway activation in the striatum and colon.ResultsYHGTD significantly improved motor and stereotypical behaviors in TD rats, decreased spontaneous activity, total travel distance, prolonged rest time, and normalized movement trajectories. It attenuated striatal neuropathology, elevated DA levels, and downregulated the expression of DRD1 and DRD2. YHGTD also suppressed microglial activation and reduced the levels of IL-1β, TNF-α, and IL-6 in the striatum, serum, and colon. Furthermore, YHGTD restored gut microbial homeostasis and reduced the abundance of proinflammatory bacterial taxa. Finally, we found that YHGTD downregulated the TLR4/MyD88/NF-κB signaling pathway in both the striatum and colon.ConclusionYHGTD alleviated TD symptoms through neuroprotective and anti-inflammatory mechanisms, accompanied by alterations in the microbiota composition, supporting its potential as a therapeutic option for TD.